PARTICIPANT AND PROCESS PREDOMINATE IN JOKO WIDODO’S SPEECH - Mubarak, Zia Hisni (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
This study is a discourse analysis of one speech from the 7th President of Indonesia Mr. Joko Widodo in an International forum. The aim of this study was to analyze the diction of words and sentences used by Joko Widodo in representing his country in APEC CEO Summit 2014. The diction of words and sentences were seen from the type of participant and process where in participant there where pronoun, noun phrase, adjective, preposition phrase and noun. In process type, there were action, event and attribution. The data to be analyzed was the transcription speech of Joko Widodo. By using descriptive analysis, this study analyzed the type of participant and process predominated in the speech. From the analysis, data were divided as 77 sentences. From those data, it was found type of participant where 23 data were noun participant, 1 data was pronoun participant, 2 data were preposition phrase participant and 6 data were adjective participant. While for process type, it was found 45 type of action process sentence and it was followed by 32 type of attribution process sentence. By the most dominant of 23 noun participant and 45 action process in the speech, it was concluded that Joko Widodo used his power as president to influence the reader and represented his country to the investor in the world forum of APEC CEO Summit 2014.